Scientific and methodological approach to assessing the effectiveness of customs control in the financial security system - Y.S. Kostyshyn (Економіка, управління та адміністрування)
The article is devoted to the study of evaluating the results of the control, which requires the development of methodological support for such an assessment and criteria for the effectiveness and control efficiency of activities. It is determined that today there is no single methodology for assessing the effectiveness of customs control, which is due to the following reasons. Firstly, customs control has its own specific assessment, requires the formation of appropriate indicators and criteria. Secondly, there is an ongoing debate about the suitability for the purpose of assessing the effectiveness, or all the same integral indicators. Thirdly, there is confusion about evaluating the effectiveness and efficiency of control as similar in content evaluation characteristics. The lack of a unified methodology for assessing the effectiveness of this control in the financial security system, the important development of performance indicators and criteria for such purposes indicates the relevance and importance of the research topic in this direction. The purpose of the article is to analyze scientific approaches to the effectiveness of control activities and develop a methodological support for assessing the effectiveness of customs control of the security system. The assessment of the advantages and disadvantages of using the methods for analyzing the effectiveness of customs control provides the opportunity to choose a scientific and methodological approach, which is a combination of the approach focused on benchmarking results using the Euclidean distance method, and a client-oriented approach, the result of which is the determination of the performance indicator of the customs standard and identification the positions of each customs office in the received state by ranking using the «sum of places» methodology. The applied application of the proposed scientific and methodological approach makes it possible to determine the efficiency of customs authorities in terms of increasing customs indicators of the level of financial security, to establish the degree of users’ satisfaction of customs services of customs security authorities.